The Taylor-Kuhn debate on the distinction between natural and social sciences - Bório de Medeiros, Bismarck (Sofia, 2025)
This paper aims to clarify the points considered relevant in the contemporary debate on the distinction between natural and human sciences carried out by Charles Taylor and Thomas S. Kuhn. Initially, we seek to elucidate relationships between Philosophical Anthropology and the effort to define the so-called Sciences of Nature and Sciences of the Spirit developed in the work of Wilhelm Dilthey – basis for Taylor in his paper Interpretation and the Sciences of Man. Thus, Kuhn will discuss Taylor's chapter in The natural sciences and the human sciences, which involves criticism of the nature and objective of the sciences including the participation of the subject, the scientific community and the hermeneutics established within the paradigm of such an area in the constitution of its interpretation. Philosophical and genealogical clarifications of their work are made, as well as analysis of convergent and divergent points in the distinction between types of science. In the end, critical comments by Hugh Lacey on the topics covered in the debate are implemented together with interpretations of Kuhn's late writings, expanding the discussion based on his own philosophy and the epistemic values present in the current scientific endeavor.
Keywords: Charles Taylor; Thomas S. Kuhn; epistemic values; hermeneutics; normal science